Eski Sana’a Geleneksel Mimarisi ve Koruma Sorunları - Hezam, Ahmed Hussein Hussein Ahmed (Fatih Sultan Mehmet Vakıf Üniversitesi, 2023)
Yemen içinde dünyanın en eski şehirleri bulunmaktadır, bunlardan birisi ise Eski Sana'a'dır. Eski Sana'a, kadim tarihi, benzersiz mimarisi ve özgün kimliği ile dünya miras listesinde yer alan Arap Yarımadası'nın en eski şehirlerinden biridir. Ne yazık ki, 1962 devriminden sonra dünyaya açılışı ile nüfus artışı, yeni teknolojinin getirdiği kullanım gereksinimleri, insanların eski evlerini terk edip yeni konutlara geçmesi, doğal afetler, yerel yönetimin disiplinsizliği ve 2011'den sonra siyasi istikrarsızlık nedeniyle ciddi hasar görmüştür. Bu tezde Eski Sana'a'nın tarihi, şehrin oluşumu, şehrin kentsel dokusunu oluşturan mimari unsurlar, geleneksel malzeme ve yapım teknikleri, dikey yerleşim sebepleri, evlerin plan tipolojisi, cephe özellikleri ele alınmıştır. Ayrıca, 1962'den bu yana yapılan koruma çalışmaları ve bu süreçte mevcut sorunların nasıl ele alındığı, ihmal, tahrip, doğal afet ve savaşın etkileri irdelenmiştir. Bunun yanında, tezin sonunda hasar gören kültür varlığı örnekleri incelenerek ayrıntılı bilgiler verilmiştir. Çalışma kapsamında Eski Sana'a için yapılan koruma ve belgeleme çalışmaları incelenmiş, bu çalışmalar tarihi süreci ele alınarak değerlendirilmiştir. 1986-1995 yıllarında yapılan kapsamlı koruma ve restorasyon çalışmasının ardından şehir maalesef ihmal edilmiştir. Koruma çalışmaları bütün şehri kapsamak yerine bina bazında yapılmıştır. 2011'den sonra şehir, bina bazında restorasyon çalışmalarından bile mahrum kalmış; ihmal ve denetimsizlik sonucunda tarihi şehre karşı ihlaller, uygunsuz müdahaleler, niteliksiz rekonstrüksiyonlar ve yeni malzeme ile uyumsuz teknikle yapılan binaların inşası gibi sorunlar yaşanmıştır. Bütün bu yapılanlar şehrin mimari bütünlüğüne zarar vermiştir. Aynı zamanda silahlı çatışma ve hava saldırıları durumu daha da kötüleştirmiştir. Bütün süreç ve koruma sorunları ele alınarak çalışmanın sonunda elde edilen sonuçlar ışığında koruma önerileri sunulmuştur.

Yemen contains within it the oldest cities in the world, and one of these cities is the ancient Sana'a. Old Sana'a is considered one of the oldest cities in the world in The Arabian Peninsula, as it has an architectural character, engineering style, and unique cultural diversity. That is why it was annexed to List of UNESCO World Heritage Cities. The city, after the revolution of 1962, opened up to the world after it was closed to it and closed on itself, and this openness led to The introduction of new technology and this technology brought with it a different style and lifestyle that the old city could not meet architecturally at that time, also the introduction of new building materials that affected the historical architectural character, and also the rapid increase in the number of residents leaving their homes in the old city and moving to live in the new city, all of these reasons It negatively affected the old city, and the damages and problems began to increase. In this message, I talked about old Sanaa from several aspects to give a complete picture of the city. Reference was made to the history of the city, its origins, its architectural heritage and its features, the style of construction, the facades of the city’s unparalleled ornate buildings, the urban planning of the city and the planning of residential houses, as well as the projects for the phases of architectural preservation and restoration that have been done for the city to this day. After that, an evaluation of these projects was made, and their positives, negatives, and shortcomings were mentioned. The problems and causes that harmed the city and hindered the completion of the architectural preservation process were discussed, and the neglect and marginalization that the city had gone through in the last years was mentioned. Then examples of damaged historical buildings were discussed. At the end of the letter, proposals for the architectural preservation of the city and protecting it from extinction were discussed. After the extensive architectural preservation process of the city between 1986 and 1995, the city was neglected, and architectural preservation and restoration operations were limited to buildings only and did not include the entire city. After the events of 2011, the city lacked preservation and restoration operations for residential buildings, let alone the city as a whole. At the same time, the absence of auditing and oversight led to an increase in violations committed by some city residents. Individual restoration operations, far from correct architectural preservation methods, have spread. The use of new building materials and techniques instead of traditional building materials and techniques has become more widespread. Also, direct aerial bombardments on the city and indirect attacks on the city’s surroundings resulted in catastrophic damage to the city. All of these reasons mentioned have harmed the city and its historical architectural fabric.
Keywords: Eski Sana'a; Geleneksel Mimari; Hasar; Koruma; Silahlı Çatışma; Yemen; Old Sana'a; Traditional Architecture; Damage; Conservation; Armed Conflict; Yemen